An Overview of Existing Experiences with Solar-Powered E-Bikes - Georgia Apostolou; Angèle Reinders; Karst Geurs (Energies, 2018)
Electric bicycles (e-bikes) are considered a sustainable alternative to automobile transportation today. The electric bike includes all the benefits that conventional bicycles offer, plus faster, more comfortable and longer trips, as well as less effort for the user. In this paper, we specifically focus on a new type of e-bike, the so-called ‘solar-powered e-bike’. Therefore, this review paper explores existing literature findings for the use of solar energy in transportation, and more specifically in e-bikes. This paper aims to capture the status of and experiences with the use of e-bikes; more specifically, with solar-powered e-bikes. It presents research conducted so far on e-bikes and solar-powered e-bikes, as well as the main technical features of the solar e-bike. Finally, it analyzes a sample of e-bikes’ and solar-powered e-bikes’ users, based on Dutch National Travel Survey data and an experimental field study conducted in 2017. Data showed that the main target group of (solar) e-bikes are commuters in the age group between 40 and 60 years old, commuting distances longer than 6 km, with a gross income higher than €2500. Solar-powered e-bikes are concluded to have potential as a sustainable way of transportation in urban areas and cities, potentially replacing the conventional means of transport.